2006
DOI: 10.1089/mdr.2006.12.284
|View full text |Cite
|
Sign up to set email alerts
|

CloacalLactobacillusIsolates from Broilers Often Display Resistance Toward Tetracycline Antibiotics

Abstract: Lactobacillus crispatus, L. reuteri, L. amylovorus, L. gallinarum, and L. salivarius subsp. salivarius strains isolated from cloacal swabs of broiler chickens derived from 20 different farms in Belgium were tested for susceptibility to tetracycline and minocycline. Acquired resistance percentages to these antibiotics were extremely high for L. crispatus, L. reuteri, L. gallinarum, and L. salivarius subsp. salivarius (75%-100%). L. amylovorus on the contrary, displayed lower resistance percentages (25%) toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 37 publications
9
20
0
Order By: Relevance
“…strains (35,39) and also for cloacal Lactobacillus salivarius subsp. salivarius isolates (5). However, to the best of our knowledge this is the first report on the coexistence of two genes encoding different mechanisms of Tc r in the same L. sakei strain.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…strains (35,39) and also for cloacal Lactobacillus salivarius subsp. salivarius isolates (5). However, to the best of our knowledge this is the first report on the coexistence of two genes encoding different mechanisms of Tc r in the same L. sakei strain.…”
Section: Discussionmentioning
confidence: 74%
“…However, in recent years a number of studies have correlated atypically high phenotypic resistances with the presence of tet genes (11,17,18,19,20,26). Tetracycline resistance in Lactobacillus has commonly been associated with the presence of tet(M) (19,20), but recently the gene coding for the efflux transporter Tet L was also described for some cloacal isolates (5). However, data about the functionality of both genes when they coexist in the same bacterium were not available until now.…”
mentioning
confidence: 99%
“…Numerous studies have already shown that TET resistance is typically transferable and a variety of plasmids have been observed (Boguslawska et al 2009;Kazimierczak et al 2009). There are currently 38 different tet resistance genes described (Cauwerts et al 2006). Gene tet(M) encoding ribosomal protection and gene tet(L) determining efflux transporter have been the most often genes identified in poultry enterococci (Boguslawska et al 2009).…”
Section: Tet Tetracycline Ery Erythromycin Mic Minimal Inhibitory Conmentioning
confidence: 99%
“…For example, L. agilis (7,57,62), L. amylovorus (11), L. crispatus (27,62), L. gallinarum (27,28,62), L. johnsonii (27,57,62), L. panis (43), L. reuteri (27,43,62), L. salivarius (27,62), L. saerimneri (62), L. vaginalis (7,57,62), P. acidilactici (1,38), P. pentosaceus (53), Enterococcus cecorum (7), E. faecium (26,31), E. faecalis (46), Enterococcus villorum (61), and Veillonella spp. (69) have previously been described as inhabitants of the chicken GIT.…”
Section: Comparison Of the Rep-pcr Protocols For Representativementioning
confidence: 99%